Evaluation of depressive-like behavior in adults mice associated with administration of subcutaneous injection of ethanol in neonatal period - Bertaglia, Everton Barbosa; Spinosa, Helenice de Souza (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2016)
The post-natal day (PND) 10 is a critical stage for brain development, comprised in the brain growth spurt (BGS) phase, characterized by periods of especially large increases of brain. In that stage, the neuronal connections are being established and chemical injuries can be toxic. Among the toxic substances, the ethanol is known to have an extensive apoptotic neurodegeneration effects throughout many regions of the developing brain, including GABAergic neurons, and this can serve to explore the function of brain regions and their relationship with depressive behavior. Objective: assess the depressive-like behavior of adult mice submitted to subcutaneous (S.C.) injection of ethanol at the PND 10